UK earth law judgments reimagining law for people and planet - Dancer, Helen ca. 20./21. Jh; Holligan, Bonnie; Howe, Helena R. 1976- (Hart Publishing, 2024)
This open access book collects 11 reimagined judgments from the UK and challenges anthropocentrism in legal decision-making across a range of legal areas. It draws from a range of Earth law approaches including rights of nature, animal rights, environmental human rights, well-being of future generations, ecocide, and reinterpretations of existing legal principles. There is an urgent need to transform our legal institutions and cultures to foster healthier relationships between people and planet. The book explores how relationships between people, place, and the more-than-human world are produced, transformed, and destroyed through law, the limits of current law and the potential for positive transformation. A paradigm shift towards planetary, ecological and multispecies approaches offers possibilities for envisioning what the future of legal decision-making could look like. Beyond the judgments, the book critically reflects on the developing field of Earth law and its potential for reshaping legal reasoning in the UK and beyond. It also offers possibilities for the future of Earth law from scholarly, educational, and policy perspectives within legal practice, training and education. The book is a must read for scholars, students, legal practitioners and activists questioning the role of law and courts as mechanisms for change. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com